2019
DOI: 10.1103/physrevapplied.11.044047
|View full text |Cite
|
Sign up to set email alerts
|

Inducing n - and p -Type Thermoelectricity in Oxide Superlattices by Strain Tuning of Orbital-Selective Transport Resonances

Abstract: By combining first-principles simulations including an on-site Coulomb repulsion term and Boltzmann theory, we demonstrate how the interplay of quantum confinement and epitaxial strain allows to selectively design nand p-type thermoelectric response in (LaNiO3)3/(LaAlO3)1(001) superlattices. In particular, varying strain from −4.9 to +2.9 % tunes the Ni orbital polarization at the interfaces from −6 to +3 %. This is caused by an electron redistribution among Ni 3d x 2 −y 2 -and 3d z 2 -derived quantum well sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 58 publications
(81 reference statements)
3
20
0
Order By: Relevance
“…Higher-level methods are beyond the scope of the present work due to the large system sizes [30,31]. Static correlation effects were considered within the DFT+U formalism [32,33] employing U = 4 eV on Ni, Cu, and Ti sites, in line with previous work [9,[34][35][36][37][38]. We confirmed that a higher value of U Cu = 6.5 eV [39] leads to largely identical results.…”
Section: Methodssupporting
confidence: 82%
“…Higher-level methods are beyond the scope of the present work due to the large system sizes [30,31]. Static correlation effects were considered within the DFT+U formalism [32,33] employing U = 4 eV on Ni, Cu, and Ti sites, in line with previous work [9,[34][35][36][37][38]. We confirmed that a higher value of U Cu = 6.5 eV [39] leads to largely identical results.…”
Section: Methodssupporting
confidence: 82%
“…We also explored the more recent many-body dispersion (MBD) technique [32], in which the atomic response functions are represented by quantum harmonic oscillators and the screened long-range many-body vdW energy is computed from the adiabatic connection fluctuation dissipation theorem within the dipole approximation. Constant-current STM images at a bias voltage V were simulated subsequently in the spirit of Tersoff and Hamann [47] as 0 -isosurfaces of the integrated local density of states (ILDOS) [12,[48][49][50][51]…”
Section: Methodsmentioning
confidence: 99%
“…For comparison, typical energy differences for quenching or altering the a − a − c + octahedral rotation pattern in YVO bulk are of the order of several hundreds of meV per Vion. Moreover, canceling the octahedral rotations in the less tilted LaNiO 3 /LAO(001) SLs requires 250-300 meV per transition metal ion [20,68]. Fig.…”
Section: Insights From First-principles Simulationsmentioning
confidence: 97%
“…In this context, simulations in the framework of density functional theory including a Hubbard-U term (DFT+U ), provide valuable insights. In particular, these calculations have successfully explained the orbital polarization profiles of charge-transfer systems such as heterostructures of nickelates [16][17][18][19][20][21][22] and cuprates [18,23]. * E.Benckiser@fkf.mpg.…”
Section: Introductionmentioning
confidence: 99%